The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/pai.12649
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers for allergy in children

Abstract: A large number of studies investigating various biomarkers for allergy have been published over the past decades. The aim of this review was to evaluate these biomarkers on their diagnostic and/or predictive value. To this date, no single or specific biomarker for allergy has been identified. As allergy is not one disease, but a collection of a number of allergic conditions, it is more plausible a combination of clinical history, clinical readouts, and diagnostic markers will be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 106 publications
0
18
0
Order By: Relevance
“…Cytokine levels and other mediators have been investigated in patients with rhinitis using the nasal fluid [8, 9, 18], either to get more insight regarding the pathogenic condition, for diagnostic purposes, or to measure therapeutic effects. However, no single or specific biomarker for AR has been identified to date, especially in children’s serum, for predicting the severity of the condition [9, 18, 19]. In children, measurements of inflammatory markers are inconsistent across the different (sampling) techniques reflecting disease heterogeneity, methodological limitations, or varying sensitivity of the biomarker detection techniques [9, 12, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine levels and other mediators have been investigated in patients with rhinitis using the nasal fluid [8, 9, 18], either to get more insight regarding the pathogenic condition, for diagnostic purposes, or to measure therapeutic effects. However, no single or specific biomarker for AR has been identified to date, especially in children’s serum, for predicting the severity of the condition [9, 18, 19]. In children, measurements of inflammatory markers are inconsistent across the different (sampling) techniques reflecting disease heterogeneity, methodological limitations, or varying sensitivity of the biomarker detection techniques [9, 12, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Especially in (young) children, reliable, non-invasive biomarkers would be valuable. Cytokine levels and other mediators have been investigated in patients with rhinitis using the nasal fluid [8, 9, 18], either to get more insight regarding the pathogenic condition, for diagnostic purposes, or to measure therapeutic effects. However, no single or specific biomarker for AR has been identified to date, especially in children’s serum, for predicting the severity of the condition [9, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Since elevated serum levels of IgE and IL-4 are considered as important biological markers of allergic diseases such as AD and athma, we also evaluated whether the sample influences the blood IgE and IL-4 concentrations of AD mice. 27) Treatment of JCE markedly diminished total IgE and IL-4 levels in the serum of DNCB-induced atopic mice. The results indicated that both topical and broad applications of JCE could improve atopic damage in murine AD models.…”
Section: Discussionmentioning
confidence: 93%
“…23,25) A powerful example of this is in the case of pimecrolimus (Elidel ® ), one representative component available for the treatment of AD, derived from ascomycin which is a natural microorganism from soil actinomycetes. 26) For this reason, plant resources including extracts, pure compounds, and phytochemical combinations have attracted continuous interest to find drug candidates for the prevention and/or treatment of atopic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relation between sIgE serum levels and adversity of the allergic responses varies, thus sIgE can occur in subjects without clinical food allergy symptoms and vice versa [ 10 12 ]. Also, other serum markers, such as IgG4 or cytokines, have been evaluated but were not validated as reliable diagnostic markers [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%